The Apoptosis of Liver Cancer Cells Promoted by Curcumin/TPP-CZL Nanomicelles With Mitochondrial Targeting Function - Li, Wanyu; Chen, Yanan; He, Kun; Cao, Tianshou; Song, Daibo; Yang, Huiling; Li, Li; Lin, Jiantao (Frontiers in Bioengineering and Biotechnology, 2022)
The mitochondrion is one of the most important cellular organelles, and many drugs work by acting on mitochondria. Curcumin (Cur)-induced apoptosis of HepG2 in liver cancer cells is closely related to the function of inhibiting mitochondria. However, the mitochondrion-targeting curcumin delivery system was rarely been reported. It is important to develop a high-efficiency mitochondrion-targeting curcumin vector that can deliver curcumin into mitochondria directly. Here, a special mitochondrion-targeting delivery system based on triphenylphosphine bromide (TPP)-chitosan-g-poly-(N-3-carbobenzyloxy-l-lysine) (CZL) with TPP functional on the surface is designed to perform highly efficient mitochondria-targeting delivery for effective liver cancer cell killing in vitro. The TEM images showed that the nanomicelles were spherical; the results of fluorescence test showed that TPP-CZL nanomicelles could promote the cellular uptake of drugs and finally targeted to the mitochondria. The results of cell survival rate and Hoechst staining showed that curcumin/TPP-CZL nanomicelles could promote the apoptosis of liver cancer cells. Curcumin/TPP-CZL nanomicelles could significantly reduce the mitochondrial membrane potential, increase the expression of pro apoptotic protein Bcl-2, and reduce the expression of antiapoptotic Bax protein, and these results were significantly better than curcumin/CZL nanomicelles and curcumin. It is a potential drug delivery system with high efficiency to target mitochondria of liver cancer cells.